МОДИФІКАЦІЯ ГЕНЕТИЧНИХ АЛГОРИТМІВ НА ОСНОВІ МЕТОДУ НЕЦЕНТРОВАНИХ ГОЛОВНИХ КОМПОНЕНТ ТА СТАНДАРТНІ ТЕСТИ - Шадура О. В. (World Science, 2019)
The purpose of this article is to develop the necessary mathematical description of the method of the uncentered principal component analysis for the optimization of the genetic algorithm. A secondary goal is to evaluate the approximations for its application for HEP data analysis and to develop its program implementation for genetic algorithm together with a new operator based on the method of the uncentered principal components (UPCA-operator) and to check its efficiency on the example benchmark tests.